Periodic Fever and Neutrophilic Dermatosis: Is It Sweet’s Syndrome? - Raheleh Assari; Vahid Ziaee; Nima Parvaneh; Mohammad-Hassan Moradinejad (Case Reports in Immunology)
A 7-year-old boy with high grade fever (39°C) and warm, erythematous, and indurated plaque above the left knee was referred. According to the previous records of this patient, these indurated plaques had been changed toward abscesses formation and then spontaneous drainage had occurred after about 6 to 7 days, and finally these lesions healed with scars. In multiple previous admissions, high grade fever, leukocytosis, and a noticeable increase in erythrocyte sedimentation rate and C-reactive protein were noted. After that, until 7th year of age, he had shoulder, gluteal, splenic, kidney, and left thigh lesions and pneumonia. The methylprednisolone pulse (30 mg/kg) was initiated with the diagnosis of Sweet’s syndrome. After about 10–14 days, almost all of the laboratory data regressed to nearly normal limits. After about 5 months, he was admitted again with tachypnea and high grade fever and leukocytosis. After infusion of one methylprednisolone pulse, the fever and tachypnea resolved rapidly in about 24 hours. In this admission, colchicine (1 mg/kg) was added to the oral prednisolone after discharge. In the periodic fever and neutrophilic dermatosis, the rheumatologist should search for sterile abscesses in other organs.